Business demography dynamics in Portugal: a semi-parametric survival analysis - Nunes, Alcina (2010)
We address the post-entry performance of new Portuguese firms by investigating the structural characteristics of the hazard and survival functions, using semi-parametric survival analysis for the total economy and its broad sectors. In order to approach the prevalence of some stylized facts and determinants of new firm survival, a new entrepreneurship database was produced, using the administrative data of Quadros de Pessoal, following the Eurostat/OECD´s internationally comparable business demography methodology. In line with the literature, we find that firms that start small and experience faster post-entry growth, face a higher probability of survival. Firm’s current size dimension matters particularly for the Services sector probability of survival. In industries characterized by high entry rates, post-entry survival is more difficult. This happens mostly in Agriculture and the Construction sectors in Portugal. We find a different result from the literature, for the effect of industry growth in survival rates. Firms operating in industries which are growing faster, seem to suffer from a higher probability of failure. The combined effect of turbulence and entry and growth variables help explaining this unexpected effect of industry growth on survival probabilities. By correcting heterogeneity, we obtain stronger magnitudes of the hazard ratios found previously.